A PERPLEXING MIXED CORTICAL AND MEDULLARY ADRENAL NEOPLASM PRESENTING WITH INDETERMINATE ADRENAL MASS - WH, Wan Mohd Hafez; MA, Masliza Hanun; WA, 1 Siti Sanaa; Mohamad, Hussain; Muda, Nor Hisham; Hashim, Norsyahinaz; Gopal, Navarasi A/P S Raja (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION A mixed cortical and medullary adrenal neoplasm originating in the adrenal gland is an exceedingly rare tumour characterized by the coexistence of cell nests from both the adrenal cortex and medulla within a singular mass, which results in the production of adrenocortical steroid hormones and catecholamines (CA). We report a case of mixed cortical medullary adrenal neoplasm presenting with indeterminate adrenal mass. CASE A 51-year-old female, with a known case of left breast mucinous carcinoma, underwent a right mastectomy and axillary clearance and completed 6 cycles of systemic chemotherapy. The computed tomography of the thorax, abdomen and pelvis (CT TAP) surveillance post-treatment revealed left adrenal indeterminate incidentaloma. Computed tomography adrenal protocol showed that the left adrenal mass was heterogeneous with a size of 1.8 x 2.2 x 2.4 cm, with a plain HU of 18 HU, absolute contrast washout of 21%, and relative contrast washout of 15%. Biochemically, both the overnight dexamethasone suppression test (ODST) and low dose dexamethasone suppression test (LDDST) were not suppressed with values of 81 nmol/L and 119 nmol/L, respectively. A 24-hour urine metanephrine collection demonstrated results within the normal range: metanephrines 0.4 umol/ day (0.1-6.2), normetanephrine 1 umol/day (0.2-1.3) and 3-methoxytyramine 0.8 umol/day (0.1-1.79). Given that the left adrenal indeterminate incidentaloma had autonomous cortisol secretion, a left adrenalectomy was performed. Remarkably, the histopathological examination (HPE) unveiled a mixed corticomedullary adrenal tumour. CONCLUSION A mixed cortical and medullary adrenal neoplasm is extremely rare. Therefore, knowledge about long-term clinical course and prognosis is limited. Long-term follow-up is recommended to assess the recurrence in the contralateral adrenal gland.